Factors Affecting the Effectiveness of Province Regional Original Income in Indonesia 2017-2020 Period - Agung Atma Darmanto (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2021)
The purpose of this study is to test, prove, and analyze the effect of Regional Taxes, Regional Levies, Other Regional Income on the Effectiveness of East Java Province Original Income for the 2017-2020 period. This study uses primary data in the form of tax report data. The sample used is 40 tax reports in the provinces of Indonesia during the period 4 2017-2020, using the purposive sampling method. The analysis used in this research is multiple linear regression analysis. Based on the results of the study, it can be ignored that the variables of Regional Taxes, Regional Levies, and Other Regional Revenues affect the Effectiveness of Regional Original Income for the 2017-2020 period. The implications and suggestions can be found after analyzing the results of research that has been carried out by the government to maintain Regional Taxes, Regional Levies and Other Regional Revenues because they affect the effectiveness of Regional Original Income. so that regional autonomy can run well.